Botrytis Fruit Rot or Gray Mold of Strawberry - J. C. Mertely; M. S. Oliveira; Natalia A Peres (EDIS)
Botrytis fruit rot (BFR), also known as gray mold, is caused by the fungus Botrytis cinerea and is one of the most important diseases of strawberry in Florida and worldwide. This 4-page document describes the symptoms and management of BFR among strawberry plants. Written by J. C. Mertely, M. S. Oliveira, and N. A. Peres and published by the UF/IFAS Department of Plant Pathology, February 2018. http://edis.ifas.ufl.edu/pp152